What is Initiative 135 for Social Housing and What Does it Mean for Housing in the City of Seattle? An exploration of perceptions of I-135 and what people in the City of Seattle think that the impact will be - Carper, Noah Cole (My University, 2023)
This is a report which examines Initiative 135 for social housing and seeks to better understand what its impact will have on the City of Seattle through perceptions of others. Issues discussed within this report include homelessness and the housing crisis in Seattle. The research questions that this report seeks to solve include: What is Initiative 135 for Social Housing and what does its recent passing mean for the City of Seattle? To research and better understand these questions, this study examines first-hand sources in the form of interviews with people related to homelessness and the housing crisis. Secondary sources include previous legislation, academic writings, and articles. These data sources work in tandem with the interviewee responses to better understand what I-135 could do for the city based on the perceptions and data collected. Data collected indicated several common themes including (1) excitement of the structure of I-135 and what it might do for Seattle, (2) logistics and utilization of resources and the upcoming growth the plan should utilize, and (3) the importance of community input when creating and operating an initiative like I-135. These themes found within the interviewee process, working with all secondary data sources, allowed for the research to provide an informed reflection and policy recommendation at the conclusion of this research. The recommendation from this study advises that the City of Seattle prioritize the construction of social housing in the near future, through utilization of I-135, and that there be more focus on resource allocation to those seeking housing via programs working with each other to get as many housed in the City of Seattle as possible.